Efektivitas Program Wirausaha Merdeka dalam Meningkatkan Kompetensi Berwirausaha Mahasiswa - Silma Salsabila; Maulidyah Indira Hasmarini (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
The Independent Entrepreneurship Program was formed with the aim of helping develop and increase entrepreneurial potential among young people, especially among students so that they can compete in the world of work or create new jobs. The method used in this research is a combination of learning by doing. Learning by doing is a learning method that focuses on direct experience or practice. The results of this research are that through this activity students are directly involved in the production process and product marketing, so that students gain an understanding of the manufacturing process in partner MSMEs. Students gain a lot of knowledge, experience, motivation and insight which is very useful as preparation for becoming an entrepreneur